Effects of Partial Mortality on Growth, Reproduction and Total Lipid Content in the Elkhorn Coral Acropora palmata - Piñón-González, Victor M.; Banaszak, Anastazia T. (Frontiers in Marine Science, 2018)
Partial mortality (PM) is increasingly common in the Elkhorn coral Acropora palmata and, depending on the causative agent, is potentially lethal. The effects of PM on growth, reproduction and total lipid content in A. palmata were studied by sampling apparently healthy (AH) colonies in comparison with colonies showing signs of PM. Branch growth rates and lesion regeneration rates were estimated using monthly photographs over a four-month period prior to the summer spawning season. No differences were found in the growth rates of colonies with PM compared to AH colonies. The areas affected by PM did not regenerate during the period of the study. Colonization of the lesions by competing species and sediment cover were documented and did not show major changes. During the spawning season, percent fertilization, egg volume and embryonic development were evaluated for comparison between AH colonies and those with PM. Total lipids were also quantified in tissues from three branches per colony. Percentage fertilization was similar in both AH colonies and those with PM. Embryonic development was normal, regardless of proximity to the lesion borders. However, egg volume was significantly lower in PM colonies than in AH colonies. Lower lipid concentrations were found at the edges of the lesions and similar to those found at the growing edges of the branches. The lack of regeneration may be explained by the low lipid concentration, because the polyps adjacent to the lesion do not have an adequate energy budget as a result of the damage. This would also affect their ability to compete against organisms that colonize the site of the lesion, a distinct situation to the rapid regeneration rates characteristic of lesions due to physical injury of the colony. Therefore, we conclude that partial mortality in A. palmata affects the colony, inducing energetic stress due to both competition and decreased quality of the eggs.